Análisis De Representaciones Gráficas Cartesianas En Libros De Texto De Biología - Artola, Eugenia Cristina; Nouveliere, Liliana Esther Mayoral; Benarroch, Alicia Benarroch (European Scientific Journal, ESJ, 2016)
Graphical representations Cartesian (RGC) are important communication tools in different areas of knowledge and in particular in the Population Biology (BP). The teaching of this area can be strongly affected by the difficulties that students encounter in the interpretation and use of the RGC. In this paper the analysis of RGC in ten textbooks and eight Secondary Education Teacher Training Biology, most widespread in the Province of Mendoza (Argentina), intended to compare and contrast their results is made. The analysis of character ontosemiotic involves both the text and the images, and uses a set of indicators associated with the semiotic concepts of relevance, appropriateness and didactic suitability, based on previous research. We conclude that the books of Teacher Education use a greater amount of RGC and generate as many positive interactions in their school books readers. They are therefore most flattering of inter-linguistic semiotic interactions and relationships between mathematical and biological language. However, they are a source of potential conflict, like school, largely because of lack of clarification of meanings of symbolic notations.